DICHOTOMY OF LANGUAGE & THOUGHT IN THE INTERPRETATION OF METAPHOR IN THE QURAN - Sardaraz, Khan; Roslan, Ali (Index Copernicus International, 2021)
Previous literature either deciphered the literary and rhetorical aspects of metaphor or focused on its conceptual basis in the interpretation of the Quran. No attempt has so far been made to harness the linguistic and conceptual metaphor approaches to provide a comprehensive interpretation of the metaphors in the Quran. This paper reviews the existing literature on the interpretation of metaphor in the Quran from different theoretical perspectives. The review reveals that the application of different theoretical approaches has led to the dissociation of language and thought in the interpretation of metaphors. The linguistic approaches miss the bulk of conventional metaphors, while the cognitive approaches ignore the linguistic aspects of metaphor. The findings also reveal that the linguistic studies of metaphor concern themselves with the rhetorical beauty of the Holy Quran, while the conceptual metaphor studies explore the generic categorization of concepts. This paper calls for a more elaborate mechanism, which can account for both the linguistic and conceptual aspects of metaphor, to fill the gap between the linguistic and conceptual knowledge in the existing literature for a comprehensive interpretation of metaphors in the Quran.